2013
DOI: 10.1016/j.visres.2013.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Crowding during restricted and free viewing

Abstract: Crowding impairs the perception of form in peripheral vision. It is likely to be a key limiting factor of form vision in patients without central vision. Crowding has been extensively studied in normally sighted individuals, typically with a stimulus duration of a few hundred milliseconds to avoid eye movements. These restricted testing conditions do not reflect the natural behavior of a patient with central field loss. Could unlimited stimulus duration and unrestricted eye movements change the properties of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
(59 reference statements)
6
18
0
Order By: Relevance
“…For example, it was shown that substitution and error rates were strongly reduced with increasing presentation times (Styles & Allport, 1986). Other studies, however, showed that unlimited viewing time only marginally changed crowding (Wallace, Chiu, Nandy, & Tjan, 2013), and high substitution rates also occurred with relatively long presentation times (2.4 s, Estes, Allmeyer, Reder, 1976;1.6 s, Zhang et al, 2012). An alternative explanation is that multiple presentations, i.e., multiple (peripheral) views of a single stimulus during one trial, caused the observed low substitution rates.…”
Section: Discussionmentioning
confidence: 98%
“…For example, it was shown that substitution and error rates were strongly reduced with increasing presentation times (Styles & Allport, 1986). Other studies, however, showed that unlimited viewing time only marginally changed crowding (Wallace, Chiu, Nandy, & Tjan, 2013), and high substitution rates also occurred with relatively long presentation times (2.4 s, Estes, Allmeyer, Reder, 1976;1.6 s, Zhang et al, 2012). An alternative explanation is that multiple presentations, i.e., multiple (peripheral) views of a single stimulus during one trial, caused the observed low substitution rates.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, masking and crowding may be determined by multiple sources of interference operating at several levels of cortical processing 51 86 and each of them might affect the task. Among these factors are a) the proximity between the target and the flankers, which depends on the eccentricity 3 4 85 , b) the duration for which the target is visible [in the fovea longer presentation times reduce crowding and masking such that at presentation times longer than 120 ms there are no crowding effects 49 51 ; in the periphery, presentation times longer than 250 ms do not affect crowding 88 even though such elongated presentation times can involve eye movements that potentially increase crowding 87 , and whether presentation times shorter than 250 ms affect peripheral crowding is still unclear, c) the temporal order (dynamics) of the presentation (backward, simultaneous, or forward masking 49 58 89 ), d) the global configuration and grouping between the mask and the target elements, where collinear configuration seems to produce the maximal effect 57 86 90 , e) contrast – where higher crowding is found with a higher contrast threshold, and f) attention 91 . Thus, crowding and masking may or may not be correlated, depending on the particular spatial-temporal parameters chosen in the study.…”
Section: Discussionmentioning
confidence: 99%
“…One of the better-known temporal properties of crowding is the effect of stimulus duration. In general, the critical spacing is larger for stimulus presented for a shorter duration than for a longer one (Chung & Mansfield, 2009 ; Kooi et al, 1994 ; Tripathy & Cavanagh, 2002 ; Wallace et al, 2013 ). Chung and Mansfield ( 2009 ) reported a reduction in the critical spacing by approximately half when the stimulus duration increased from 53 to 1000 ms (for targets and flankers with the same contrast polarity).…”
Section: Introductionmentioning
confidence: 99%